Use of vermicomposting biotechnology for recycling organic wastes in agriculture - Gunindra Nath Chattopadhyay (International Journal of Recycling of Organic Waste in Agriculture)
Recent trend of declining sustainability in agricultural production is appearing as a major threat to most of the Asian countries. To combat the situation, increasing importance is now being paid on incorporation of organic materials for rejuvenating the health condition and, hence, the productivity of these soils. Large scale availability of conventional organic manures being a big problem nowadays, major attention is being paid on recycling of different kinds of organic wastes for this purpose. Apart from abatement of environmental pollution, such reuse of organic wastes in agriculture helps in the improvement of various physical, chemical and biological properties of the soils and, thus, helps in sustaining the soil health. While recycling different organic wastes in agriculture, it is essential to process the materials through an adequate period of composting for improving their usability in the soils. However, due to some short comings of traditional composting systems, the technology of recycling of organic wastes has not been widely accepted so far. Under this situation, vermicomposting has recently emerged as a simple but efficient biotechnology for recycling wide ranges of organic wastes with the help of some specific groups of earthworms. In view of the growing popularity of this biotechnology, various aspects of waste recycling in agriculture through vermicomposting have been dealt in this communication.